Bilateral Brachial Neuritis Following Diphtheria, Tetanus and Pertussis Vaccination: Case Report - AKYÜZ, GÜLSEREN DERYA; YAĞCI, İLKER (ORTADOGU AD PRES & PUBL CO, 2010)
Brachial plexopathy in children is commonly caused by obstetrical complications. Only few cases were reported as brachial neuritis which is also known as Personage Turner disease. Antecedent infection, viral diseases, trauma, surgery, and immunization may be the possible etiologic factors causing brachial neuritis. In this case report, a 6 months old child who was referred to our outpatient clinic with bilateral hand, arm and shoulder weakness which occurred after immunization with diphtheria, tetanus and pertussis (DTP) vaccine at 5 months of age is presented. The case was diagnosed as bilateral brachial neuritis according to clinical and electrophysiological data and no possible etiologic factors could be associated with the clinical condition except DTP vaccination.
Keywords: Brachial plexus neuritis; immunization; diphtheria-tetanus-pertussis vaccine; PALSY